2013
DOI: 10.4187/respcare.02654
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of Four Different Devices for Secretion Mobilization: Acapella Choice, Green and Blue Versus Water Bottle

Abstract: BACKGROUND: Secretion removal is a key issue in patients with respiratory diseases, and is known to be most effective at vibration frequencies of ϳ13 Hz and with the greatest amplitudes possible. The Acapella devices and the water bottle are used for secretion removal in daily clinical practice but without detailed knowledge on optimal settings. The aim of this study was to evaluate the 3 different Acapella devices and the water bottle at various settings and flows to determine the optimal devices and settings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 4 publications
1
13
0
2
Order By: Relevance
“…In Tube, however, there was also a significant pre-post main effect for mean flow during voicing If flow is likely to have an impact on static pressure for Acapella®, and we have observed that static pressure is correlated with peak to peak amplitudes for the device, it is expected that flow is also likely to affect oscillatory pressures. Wistbacka et al 21 found that variations in flow positively affected the frequency and peak-to-peak amplitude modulation of bubbling in Tube exercises, and similar findings were also demonstrated by Mueller et al 22 using Acapella®. In the present study, Acapella® offered not only a significantly greater mean peak-to-peak amplitude than Tube, which participants subjectively reported as more 'intense', but one which was significantly more regular (i.e.…”
Section: Electroglottographic Variablessupporting
confidence: 62%
See 1 more Smart Citation
“…In Tube, however, there was also a significant pre-post main effect for mean flow during voicing If flow is likely to have an impact on static pressure for Acapella®, and we have observed that static pressure is correlated with peak to peak amplitudes for the device, it is expected that flow is also likely to affect oscillatory pressures. Wistbacka et al 21 found that variations in flow positively affected the frequency and peak-to-peak amplitude modulation of bubbling in Tube exercises, and similar findings were also demonstrated by Mueller et al 22 using Acapella®. In the present study, Acapella® offered not only a significantly greater mean peak-to-peak amplitude than Tube, which participants subjectively reported as more 'intense', but one which was significantly more regular (i.e.…”
Section: Electroglottographic Variablessupporting
confidence: 62%
“…As with static pressure, the range of inter-subject peak-to-peak amplitudes for Acapella® in Figure 2 is larger than for Tube. Following Mueller et al 22 , this range of amplitudes is likely to do with differences in flow used by different participants when exercising with Acapella®. Wistbacka et al 21 found that the peak-to-peak amplitude in Tube exercises plateaued once submersion depths exceeded 3cm of water and flow exceeded 0.2L/s.…”
Section: Electroglottographic Variablesmentioning
confidence: 98%
“…All 5 devices investigated produced oscillation frequencies of 11-17 Hz, comparable with those of the Acapella (DHD Healthcare, Wampsville, New York) and Flutter (VarioRaw SA, Aubonne, Switzerland) devices. [10][11][12] Oscillation frequencies similar to ciliary beat frequency of 13.2 Hz 13 may aid secretion clearance by increasing the amplitude and frequency of the cilia, potentially increasing mucociliary transport. 11 A study investigating the clearance of mucus in the trachea of dogs found that the enhancement of clearance was most pronounced if the oscillation frequency was between 11 and 15 Hz, 14 whereas another study investigating the Flutter device in children and adults with cystic fibrosis found that airway oscillations of approximately 19 Hz reduced sputum viscoelasticity in vitro, 15 making it easier to move airway secretions.…”
Section: Discussionmentioning
confidence: 99%
“…The Acapella devices elicit higher vibration amplitudes (5 to 8 cmH 2 O) than the water bottle (1.8 cmH 2 O). The Acapella devices may be more efficient for secretion mobilization than the water bottle, because they elicit greater amplitude of vibrations [12].…”
Section: Discussionmentioning
confidence: 99%